2023
DOI: 10.3390/molecules29010234
|View full text |Cite
|
Sign up to set email alerts
|

PPy-Coated Mo3S4/CoMo2S4 Nanotube-like Heterostructure for High-Performance Lithium Storage

Fei Tang,
Wei Jiang,
Jingjing Xie
et al.

Abstract: Heterostructured materials show great potential to enhance the specific capacity, rate performance and cycling lifespan of lithium-ion batteries owing to their unique interfaces, robust architectures, and synergistic effects. Herein, a polypyrrole (PPy)-coated nanotube-like Mo3S4/CoMo2S4 heterostructure is prepared by the hydrothermal and subsequent in situ polymerization methods. The well-designed nanotube-like structure is beneficial to relieve the serious volume changes and facilitate the infiltration of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The elemental mapping analysis (Figure 1i-l) shows the rectangular distribution of Mo (green), Fe (red), and S (blue) in MoS 2 /FeS 2 . The intimate contact interface between MoS 2 and FeS 2 significantly optimizes the lithium-ion transport path and enhances lithium-ion storage performance [24]. TEM is conducted to demonstrate the presence of an interfacial structure betwee MoS2 and FeS2.…”
Section: Resultsmentioning
confidence: 99%
“…The elemental mapping analysis (Figure 1i-l) shows the rectangular distribution of Mo (green), Fe (red), and S (blue) in MoS 2 /FeS 2 . The intimate contact interface between MoS 2 and FeS 2 significantly optimizes the lithium-ion transport path and enhances lithium-ion storage performance [24]. TEM is conducted to demonstrate the presence of an interfacial structure betwee MoS2 and FeS2.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, regarding the electrostatic force that might have occurred from Fe + between particles, as mentioned above [ 54 , 55 ], this interaction force may disrupt sheet-like forming and increase porosity in the PPy structure [ 59 ]. Some works reported that a specific higher porous PPy structure represented a higher surface area and an increase in its electronic properties [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this investigation was the development of advanced BFO and BFOpolypyrrole (PPy) electrodes with high active mass loading for energy storage in supercapacitors. PPy is a conductive redox-active polymer that is used for many advanced energy storage and catalytic applications [26][27][28][29][30][31]. This polymer and its composites exhibit good charge storage properties, which are especially important for supercapacitors [31,32].…”
Section: Introductionmentioning
confidence: 99%